2009
DOI: 10.1111/j.1365-2672.2008.04141.x
|View full text |Cite
|
Sign up to set email alerts
|

How much ozone bactericidal activity is compromised by plasma components?

Abstract: Aims: Evaluation of bactericidal effect of different concentrations of ozone\ud when used (a) as a gas, or (b) dissolved in saline. The addition of hydrogen\ud peroxide or 4-hydroxynonenal dissolved in saline was also tested, as well as the\ud effect of human plasma.\ud Methods and Results: Staphylococcus aureus, methicillin-resistant Staph. aureus\ud (MRSA), and Pseudomonas aeruginosa, suspended in their culture media were\ud tested. While all bacteria suspended in protein-free saline were killed at high\ud o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 34 publications
(43 reference statements)
2
41
0
Order By: Relevance
“…In fact, these results are consistent with those of Burgassi et al [27], showing that the AHT enriched with ozone, even at highest ozone concentration (80 µg/ml), is not able to oxidize and destroy circulating bacteria in the blood.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In fact, these results are consistent with those of Burgassi et al [27], showing that the AHT enriched with ozone, even at highest ozone concentration (80 µg/ml), is not able to oxidize and destroy circulating bacteria in the blood.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, these authors suggested the incompatibility of using whole blood because it coagulates in the presence of a bacterial suspension [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozone can be easily consumed by oxidizable organic stuff and reductants present in its surroundings (13). Notably, in our in vitro experiments, NBOW that had been stored frozen for 1 year killed one of the most resistant bacteria, M. smegmatis, within 15 min; however, E. coli W3110 was not entirely killed even after a 60-min exposure.…”
Section: Discussionmentioning
confidence: 83%
“…In the past it has been claimed that ozone therapy allows seroconversion in HIV patients but we have not confirmed this result [30] . Our recent study [31] , aiming to evaluate how much ozone bactericidal activity is inhibited by the presence of plasma antioxidants, has confirmed that ozone cannot inactivate bacteria or/and viruses in vivo, particularly when pathogens are intracellular owing to the high content of GSH and antioxidant enzymes. Thus the previous dream to sterilize blood from all pathogens, especially viruses, is insubstantial because theoretically we would need such high ozone concentrations to kill blood cells before the intracellular viruses or parasites.…”
mentioning
confidence: 99%